Kizil on the silk road : crossroads of commerce & meeting of minds - Ghosh, Rajeshwari; National Centre for the Performing Arts (Mumbai, India); Marg Publications (Mumbai : Marg Publications on behalf of the National Centre for the Performing Arts, 2008)
Contributed articles on the paintings at Kizil Caves, China
" vol. 59, no.3" -- T.p. verso ; simultaneously issued in serial format as an issue of Marg
Includes bibliographical references and index
Keywords: Buddhist mural painting and decoration -- China -- Kizil Caves